Pengetahuan Dan Sikap Ibu Tentang Diare Pada Balita Di Desa Mamulusan Kecamatan Liangkabupaten Banggai Kepulauan - Abd. Rifai; Agustinus Talindong; Desnonliana Mangasake (Universitas Widya Nusantara, 2024)
According to the World Health Organization, the death rate of children under the age of 5 years is equal to 1.5 million, child deaths due to diarrhea, 78% occur in Asia, Africa and Southeast Asia, but in Indonesia the death rate of children under five due to diarrhea is still relatively high and Indonesia is still ranked 6th highest after Singapore. The purpose of this study is to find out the knowledge and attitude of mothers about diarrhea in toddlers (3-5 years) in Mamulusan Village, Liang District, Banggai Islands Regency. Types of descriptive research variables of knowledge and attitudes. By collecting primary and secondary data using a quartier, the analysis was used, namely univariate analysis, the population in the study, namely mothers with toddlers, amounted to 78, out of 44 respondents. Sampling uses purposive sampling. The results of the study showed that mothers' knowledge about diarrhea was mostly poor, amounting to 19 respondents (43.2%), sufficient knowledge as many as 13 respondents (29.5%), and good 12 respondents (27.3%). For the attitude of respondents about diarrhea that is good, there are 13 respondents (29.5%), 26 respondents (59.1%) and 5 respondents (11.4%). The conclusion in the study is that most of the knowledge and attitudes of mothers under five in Mamulusan Village are good. It is hoped that this research can motivate the community, especially mothers of toddlers, to increase knowledge and attitudes.